2017
DOI: 10.1016/j.jtcme.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of novel dietary supplement on metabolism in vitro and in vivo

Abstract: Obesity is an increasingly prevalent and preventable morbidity with multiple behavioral, surgical and pharmacological interventions currently available. Commercial dietary supplements are often advertised to stimulate metabolism and cause rapid weight and/or fat loss, although few well-controlled studies have demonstrated such effects. We describe a commercially available dietary supplement (purportedly containing caffeine, catechins, and other metabolic stimulators) on resting metabolic rate in humans, and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
1
6
1
Order By: Relevance
“…While formulation differences certainly exist, the impact of epinephrine increases in the present study are an important mechanistic link to the reported increases in energy expenditure and oxygen consumption by the present study and the work of Vaughan et al (Vaughan et al, 2015). In light of our findings, it is tempting to speculate that the caffeine contained within the TS formulation was the primary contributor to the reported increases in oxygen consumption, epinephrine and energy levels in the present study, however, we acknowledge that our study was not designed to explicitly highlight the impact of any single ingredient, including caffeine.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…While formulation differences certainly exist, the impact of epinephrine increases in the present study are an important mechanistic link to the reported increases in energy expenditure and oxygen consumption by the present study and the work of Vaughan et al (Vaughan et al, 2015). In light of our findings, it is tempting to speculate that the caffeine contained within the TS formulation was the primary contributor to the reported increases in oxygen consumption, epinephrine and energy levels in the present study, however, we acknowledge that our study was not designed to explicitly highlight the impact of any single ingredient, including caffeine.…”
Section: Discussionsupporting
confidence: 74%
“…A priori statistical power and sample size calculations were completed, but the measured effects were not as great as expected based on previous (similar) studies. For example, Vaughan et al, 2015 administered TS to ten healthy, collegeaged men and reported a significant increase in oxygen consumption, while the present study employed 15 participants, but failed to report any between-condition effects. This is largely due to the smaller measured effect in the present study versus the measured effects in the Vaughan paper.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations